PECS (Picture Exchange Communication System) dalam kajian neurolinguistik untuk mengatasi gangguan berbahasa bagi anak disleksia - Ari Purnomo Endah Aflahani; Aliva Rosdiana (JURNAL LENTERA ANAK, 2021)
Neurolinguistic Studies is an interdisciplinary study in the field of Linguistics and also in the field of Medicine which examines the relationship between the human brain and language abilities. Picture Exchange Communication System (PECS) is considered a solution to overcome language and literacy disorders in dyslexic children. This study aims to reveal language disorders both speaking and reading for children with dyslexia and their solutions using the Picture Exchange Communication System (PECS). This type of research is descriptive qualitative by taking samples as research subjects, namely elementary school students with dyslexia disorders. This study uses a single subject experimental method or single subject research (SSR) with a sample of eight students with dyslexia as a subject. The research stages that have been achieved include: (1) Introduction, (2) Theoretical Neurolinguistic Studies applied to dyslexic children, (3) Empirical tests, and (4) Products applied. The results obtained from the use of the Picture Exchange Communication System (PECS) method can motivate dyslexic students to practice and improve reading and writing skills.